Early Sandbian (Late Ordovician) conodonts from the Yenwashan Formation, western Zhejiang, South China - Zhen, Yong Yi; Zhang, Yuandong (张元动); Percival, Ian G. (Alcheringa: An Australasian Journal of Palaeontology, 2009)
Zhen, Y.Y., Zhang, Y.D. Percival, I.G., June, 2009. Early Sandbian (Late Ordovician) conodonts from the Yenwashan Formation, western Zhejiang, South China. Alcheringa 33, 133-161. ISSN 0311-5518. Conodonts are documented from the basal Yenwashan Formation at the Huangnitang Section (the GSSP section for the base of the Darriwilian), exposed near Changshan County town in western Zhejiang. The fauna consisting of 14 species is dominated by Pygodus anserinus, Periodon aculeatus, Protopanderodus cooperi, Costiconus ethingtoni and Dapsilodus viruensis. Both P. anserinus and P. cooperi are revised as having a septimembrate apparatus. The Pa element of P. anserinus has a morphology that varies from the primitive form with node-like denticles of the fourth row only developed on the distal part of the platform, to the advanced form with a well-developed fourth row of denticles. Association of these two morphotypes of P. anserinus, and the absence of P. serra and P. xinjiangensis in the basal Yenwashan Formation, suggests correlation of this level with the upper part of the P. anserinus Biozone (earliest Late Ordovician). This age determination agrees with the FAD of Nemagraptus gracilis immediately below in black shales intercalated with thinly bedded limestones at the very top of the underlying Hulo Formation, and provides new data for correlation with the graptolite biozone.